2019
DOI: 10.1080/21691401.2019.1643732
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 inhibits proliferation and promotes apoptosis by regulating HMGB1 in uterine fibroid cells

Abstract: To study the effects of ginsenoside Rb1 and the molecular mechanisms on proliferation and apoptosis of uterine fibroid cells, Rb1 þ pc DNA3.1, Rb1 þ pc DNA3.1-HMGB1, si-NC or si-HMGB1 was transfected into uterine fibroid cells by liposome method; the inhibitory rate and proliferation of human uterine fibroid cells were detected by MTT assay; apoptosis of uterine fibroid cells was detected by flow cytometry assay; HMGB1 protein expression in uterine fibroid cells was detected by Western blot assay. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is likely that Korean ginseng will also reduce HMGB1 levels, because cytokines under the control of NF-kB, such as TNF and IFN-g, induce HMGB1 [104]. In fact, ginsenoside has been shown to decrease HMGB1 levels in a human uterine fibroid cell model [105]. Its direct anti-viral function has also been proven against Influenza strain H1N1, which was prevented from attaching to host α 2-3' sialic acid receptors by ginsenoside interaction with viral Haemagglutinin when administered topically to the viral infection site intranasally [106].…”
Section: Panax Ginseng Cameymentioning
confidence: 99%
“…It is likely that Korean ginseng will also reduce HMGB1 levels, because cytokines under the control of NF-kB, such as TNF and IFN-g, induce HMGB1 [104]. In fact, ginsenoside has been shown to decrease HMGB1 levels in a human uterine fibroid cell model [105]. Its direct anti-viral function has also been proven against Influenza strain H1N1, which was prevented from attaching to host α 2-3' sialic acid receptors by ginsenoside interaction with viral Haemagglutinin when administered topically to the viral infection site intranasally [106].…”
Section: Panax Ginseng Cameymentioning
confidence: 99%
“…Ginsenosides, such as Rb 1 and Rg 1 , a group of triterpenoid saponins, are also widely used to treat diseases of the nervous system [Alzheimer's disease (Lin et al, 2019), Parkinson's disease (Zhang et al, 2018), and cerebral ischemia (Dong et al, 2017; Yan et al, 2018)], tumors (Zhang et al, 2019), and diabetes and their complications (Shao et al, 2019; P. Zhou, Xie, et al, 2019). However, numerous studies have found that Rb 1 and Rg 1 exhibit lower oral bioavailability in vivo (Peng et al, 2012; Zhou, Wu, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%